2021
DOI: 10.1080/10641963.2021.1896725
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial angiogenesis induced by exercise training involves a regulatory mechanism mediated by kinin receptors

Abstract: Fang & Qiwen Wang (2021): Myocardial angiogenesis induced by exercise training involves a regulatory mechanism mediated by kinin receptors, Clinical and Experimental Hypertension,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Stimulation-induced angiogenesis due to exercise includes angiogenic factors such as VEGF and FGF-2. It has been suggested that FGF-2 plays an important role in exercise-induced cardiac angiogenesis (14). Consistent with the results of the present study, a study was conducted on the elderly to explore the effect of 8 weeks of running on angiogenic changes and molecular mediators associated with myocardial angiogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…Stimulation-induced angiogenesis due to exercise includes angiogenic factors such as VEGF and FGF-2. It has been suggested that FGF-2 plays an important role in exercise-induced cardiac angiogenesis (14). Consistent with the results of the present study, a study was conducted on the elderly to explore the effect of 8 weeks of running on angiogenic changes and molecular mediators associated with myocardial angiogenesis.…”
Section: Discussionsupporting
confidence: 87%